Prognostic Significance of FDG PET/CT in Esophageal Squamous Cell Carcinoma in the Era of the 8th AJCC/UICC Staging System - Lee, Hyunjong; Lee, Kyung Soo; Min, Yang Won; Kim, Hong Kwan; Zo, Jae Ill; Shim, Young Mog; Choi, Joon Young (Frontiers in Oncology, 2022)
Recently, the American Joint Committee on Cancer (AJCC)/Union for International Cancer Control (UICC) staging system was updated for its 8th edition. F-18 fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) is a useful imaging tool to diagnose and predict prognoses for esophageal cancer. However, there was no previous study to explore the role of FDG PET/CT in the staging system based on the 8th edition. The prognostic value of FDG PET/CT was investigated in patients with esophageal squamous cell carcinoma (SqCC) considering the new 8th AJCC/UICC staging system. Subjects were 721 patients with esophageal SqCC undergoing pretherapeutic FDG PET/CT. Clinico-pathological variables and the maximum standardized uptake value (SUVmax) of the primary tumor were included in survival analysis. Subgroup analysis was performed to compare hazard ratios according to pathological stage and SUVmax. A new staging classification including FDG uptake was proposed. In multivariate survival analysis, pathological stage and SUVmax of the primary tumor were selected as independent prognostic factors for overall survival in both the 7th and 8th editions. The proposed new staging system showed better discrimination for overall survival between stage I and II than did the conventional staging system (hazard ratios: 2.250 vs 1.341). The FDG uptake of the primary tumor was found to be an independent prognostic factor along with pathological stage based on both 7th and 8th AJCC/UICC staging systems in patients with esophageal SqCC. The suggested new staging system including SUVmax was better for predicting prognoses than the conventional staging system.